Kebijakan Ekonomi BRICS Penyeimbang Global terhadap Dominasi Barat: Doni Hendrik, Hengki Fernanda - FERNANDA, ST., M.Si, HENGKI (LPPM STIA Nusantara Sakti, 2024)
This article examines the economic policies of the BRICS countries (Brazil, Russia, India, China and South Africa) and their role in balancing the global economy. This research will discuss how BRICS member countries use their economic power to reorganize global economic governance and reduce dependence on financial institutions such as the IMF and World Bank and initiate reforms in various sectors including energy and international trade. This research will identify forms of economic cooperation that focus on global economic inclusiveness by highlighting BRICS efforts to develop a new reserve currency to reduce the dominance of the US dollar and strengthen international trade. This research finds that the innovative economic policies and collaborative strategies of the BRICS countries are to create a more multipolar, balanced and sustainable global economic order. This research will contribute to understanding BRICS economic policies and their impact on the global economy